Analisis Pengaruh Konflik Hubungan Kerja Terhadap Motivasi Kerja Karyawan Studi Empirik Pada Industri Kerajinan Rotan Desa Trangsan Gatak Sukoharjo Jateng - Sujadi Lukman Hakim; Siti Fatimah Nurhayati (Conference In Business, Accounting, And Management (CBAM), 2012)
The research examined the impact relation conflict with the setting of high shool institution namely the home industrial Trangsan, Gatak, Sukharjo. The objective was to analyze whether the variable of worker behavioral attributes model of relation conflict consisting of miscommunication, naive realisme, intervence, faulty attribution, disagreement and negative emotion significanly affecting the work motivation. The sampling as many as 48 persons was taken by using purposive method. They comprised the managers whose qualifications were as workers of administration unit in university. From the 52 persons taken as samples through questioner sheets, 50 quistioner sheets were returned but one of them was damaged. Therefore, there wereonly 48 quistioner sheets which were valid to be analyzed. The result of regression analysis by using the instrument called the program SPSS version 12.00 showed that miscommunication and naive realisme significanly negative affecting the work of motivation. Whereas the others variable such as negative emotion, intervence, faulty attribution, disagreement have effect positively toward the work of motivation.Keywords : Faulty attribution, miscommunication, naive realisme, intervence, disagreement and negative emotion and the work of motivation.